13s+4=-3(3-4s)-1

Simple and best practice solution for 13s+4=-3(3-4s)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13s+4=-3(3-4s)-1 equation:


Simplifying
13s + 4 = -3(3 + -4s) + -1

Reorder the terms:
4 + 13s = -3(3 + -4s) + -1
4 + 13s = (3 * -3 + -4s * -3) + -1
4 + 13s = (-9 + 12s) + -1

Reorder the terms:
4 + 13s = -9 + -1 + 12s

Combine like terms: -9 + -1 = -10
4 + 13s = -10 + 12s

Solving
4 + 13s = -10 + 12s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-12s' to each side of the equation.
4 + 13s + -12s = -10 + 12s + -12s

Combine like terms: 13s + -12s = 1s
4 + 1s = -10 + 12s + -12s

Combine like terms: 12s + -12s = 0
4 + 1s = -10 + 0
4 + 1s = -10

Add '-4' to each side of the equation.
4 + -4 + 1s = -10 + -4

Combine like terms: 4 + -4 = 0
0 + 1s = -10 + -4
1s = -10 + -4

Combine like terms: -10 + -4 = -14
1s = -14

Divide each side by '1'.
s = -14

Simplifying
s = -14

See similar equations:

| 140+25x=140+25x | | 0x+6y=-24 | | 2ln(x)+3=9 | | 75(3/4) | | F(x)=1x^2+2x+2 | | 9x-14=52 | | 4(2n+3)=7(4n+1)+9 | | 6+y=14-3y | | x+3(3x+1)+x+9= | | 48-2y=4y | | x^(-1/13)=1/2 | | 3sin(2x-1)-1=0 | | Y=9.25*6x | | x^(-1/13=1/2 | | 27m^2+36m+12= | | 5i=15u | | 225+3y+3y=120 | | 4/9=5/(n-5) | | 700-3w=450+15w | | x^(1/13)=-1/2 | | 3.5x=4.2 | | -15r+21-(5r-3)=44 | | 14+w=24+6w | | 2x+11=3x-40 | | -9(x+4)=81 | | 2(2x+11)=3x+8 | | 4/9=5/n-5 | | -6n+21=12-15n | | 4i=8x | | 4i=4x | | 5x=-5-10 | | 0.12(y-7)+0.02y=0.18y-0.9 |

Equations solver categories